2019
DOI: 10.1590/1807-3107bor-2019.vol33.0072
|View full text |Cite
|
Sign up to set email alerts
|

A prospective case series on surgical treatment of circumferential and semi-circumferential defects due to peri-implantitis

Abstract: A prospective case series on surgical treatment of circumferential and semi-circumferential defects due to peri-implantitis Abstract: Different surgical treatment strategies for peri-implantitis with the use of graft material and membranes have been suggested without any longitudinal remarkable success rate. The present preliminary study was aimed to analyze a new clinical approach based on the disinfection of the implant connection, the disinfection of the implant surface and GBR approach in the treatment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Peri-implantitis (PI), also known as implant infection, is a biological complication involving soft and hard tissues around the osseointegrated implants [ 5 , 6 ]. It consists of a polymicrobial anaerobic infection which causes a chronic inflammatory process [ 5 , 7 ], leading to the formation of a peri-implant pocket with consequent bone loss [ 8 , 9 ]. PI prevalence has been recently estimated to be involved in more than 12% of the implant treatments in the clinical practice [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peri-implantitis (PI), also known as implant infection, is a biological complication involving soft and hard tissues around the osseointegrated implants [ 5 , 6 ]. It consists of a polymicrobial anaerobic infection which causes a chronic inflammatory process [ 5 , 7 ], leading to the formation of a peri-implant pocket with consequent bone loss [ 8 , 9 ]. PI prevalence has been recently estimated to be involved in more than 12% of the implant treatments in the clinical practice [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The studies were from four categories: controlled intervention studies [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ], observational cohort and cross-sectional studies [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], and case series/case reports studies [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…No conclusions could be drawn due to the high heterogeneity between the current studies. Canullo et al [21] deduced in a prospective study that they obtained better results when the prosthetic restoration was removed. Daugela et al [35] reported no statistically significant differences between removing the prosthesis or not during the healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Recent meta-analyses, such as that of Lollobrigida et al [34], revealed that there are only two studies [21,35] that compare the effect of healing in peri-implant defects, removing prosthetic restorations or not after regenerative surgery in peri-implantitis, showing better clinical results when submerged healing and barrier membranes were performed, and furthermore indicating that rough surfaces can improve reosseointegration when compared to smooth surfaces. This confirms what is described by Schwarz et al [29], who found that submerged healing is preferable for several reasons, since there is complete isolation in the regenerated area, better soft tissue healing, and a decrease in the risk of postoperative infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation